"How Is My English?": Chinese University Students' Attitudes Toward China English and Their Identity Construction. (August 2021) - Pan, Haiying; Liu, Chang; Fang, Fan; Elyas, Tariq
Due to the spread of the English language in various domains and the fact that English is used as a global language, researchers and educators have started to rethink the models and aims of English language teaching in different settings. From the World Englishes (WE) perspective, this study investigated the attitudes of Chinese university students toward the localized variety of "China English, " as well as the students' identity construction and negotiation during their English language learning journey. Data were collected through a questionnaire completed by 190 respondents and interviews conducted with 20 participants. The findings revealed the students' positive attitudes toward China English and non-conformity to English as a native language (ENL). This further reflected the communicative function of English and the students' interest in forming a Chinese cultural identity. However, the students also showed self-contradictory attitudes toward China English, as most did not want to be clearly identified as Chinese when using English. The data revealed some important reasons for this attitudinal conflict, including the belief that ENL is the standard form of English, as well as the students' desire to develop an identity as competent second language learners of English. The findings suggest the importance of increasing awareness of the global spread of English and reforming English curricula and assessment in contexts where local varieties of English are emerging.